Injury Types and Incidence Rates in Precollegiate Female Gymnasts: A 21-Year Experience at a Single Training Facility. Issue 4 (6th April 2015) - Saluan, Paul; Styron, Joseph; Ackley, J. Freeland; Prinzbach, Arianna; Billow, Damien
Background: With childhood sports opportunities continuing to increase at an enormous rate along with participation starting at younger ages, the number of female participants in sports has increased in paramount fashion over the past few decades. A review of the current literature reveals a very small number of studies (<30) that document specific injuries suffered by competitive female gymnasts. Purpose: To retrospectively evaluate the incidence of various injuries and injury rates for different gymnast levels among young precollegiate female gymnasts over a 21-year period, from 1985 to 2005. Study Design: Descriptive epidemiological study. Methods: This institutional review board–approved study retrospectively evaluated young, precollegiate female gymnasts over a 21-year period. Gymnasts were stratified into 1 of 4 competition levels based on the number of hours spent training. In addition to the frequency of injuries and hours trained, data collected on each gymnast included the following: age at the time of injury, body part injured, laterality of the injury, and diagnosis. Results: Over the 21-year period, 3681 new injuries were evaluated by a single physician. The injury incidence (2.155 per 1000 exposure hours) was slightly lower when compared with previously reported injury rates. There were 1, 452, 574 total exposure hours documented from training facility records. The injury rate per 1000 exposure hours was 2.859 for elite, 2.820 for high-level, 1.667 for intermediate, and 0.687 for novice gymnasts. The lower extremity was injured more often than the upper extremity (60.9% compared with 22.6% of total injuries). This difference was statistically significant across all levels. Conclusion: The injury incidence in this study was 2.155 per 1000 exposure hours. This was slightly lower when compared with previously reported injury rates. Although those studies only lasted 3 years or less, the injury rates can be directly compared because they are reported as injuries per 1000 training hours. Clinical Relevance: With the variability in data available and limited studies reported, a conclusive analysis is needed because of the long-term effects of injury seen on gymnasts, such as early degenerative disorders, cost of injury treatment, and reduction of well-being. In our 21-year study, we found the incidence of injury was slightly lower than that shown in prior shorter studies. In addition, we were able to evaluate specific injuries seen in this population over that time period. Also, this extended study revealed the longitudinal nature of a series of injuries over a period of time that has not been seen in other studies, thus giving insight into the effects of increased gymnastics in the young, female, adolescent population, which could be potentially used in guidelines for gymnasts in the future.